Yolk sac and its effects on fetal prognosis - Das, Sankar Kumar; Roy, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The yolk sac is the first extra embryonic structure that becomes sonographically visible within the gestational sac. It provides nutritional, metabolic, endocrine, immunologic, and hematopoietic functions during organogenesis in embryonic life, before placental circulation is established. Spontaneous abortion rates are significantly elevated where the yolk sac volume falls outside the 5th to 95th percentile. Abnormal morphological appearance of the yolk sac is also suggestive of serious growth disorders of the fetus. The aim is to find out the predictive value of yolk sac on outcome of the pregnancy and any probable relationship of the yolk sac pattern with the gender of the fetus. Methods: The present study was carried out on fifty patients in their first trimester of pregnancy. Patients were divided into their respective gestational age groups and according to the morphology of the yolk sac. Data were compared using Chi square test. p value less than 0.5 was considered significant. Results: Out of the fifty patients, twenty-nine were having regular yolk sac, eleven were with irregular yolk sac and ten were with hyperechoic yolk sac. There was a significant number of fetal demise in the cases with hyperechoic and irregular yolk sac. Also, there were hardly any live births in the few cases in which the yolk sac was either too small or too big. Conclusions: The present study concludes that along with a yolk sac of a given normal range for its size, it should also be of normal morphology for better prognosis of the pregnancy. Also, the increase in the number of female live births needs further studies as to whether there is any abnormality in the Y chromosome causing morphologically abnormal yolk sac and subsequent fetal demise.